BBX7 interacts with BBX8 to accelerate flowering in chrysanthemum - Yiwen Zhai; Yuqing Zhu; Qi Wang; Guohui Wang; Yao Yu; Lijun Wang; Tao Liu; Shenhui Liu; Qian Hu; Sumei Chen; Fadi Chen; Jiafu Jiang (Molecular Horticulture, 2023)
Abstract The quantitative control of FLOWERING LOCUS T (FT) activation is important for the floral transition in flowering plants. However, the flowering regulation mechanisms in the day-neutral, summer-flowering chrysanthemum plant remain unclear. In this study, the chrysanthemum BBX7 homolog CmBBX7 was isolated and its flowering function was identified. The expression of CmBBX7 showed a diurnal rhythm and CmBBX7 exhibited higher expression levels than CmBBX8. Overexpression of CmBBX7 in transgenic chrysanthemum accelerated flowering, whereas lines transfected with a chimeric repressor (pSRDX-CmBBX7) exhibited delayed flowering. Yeast single hybridization, luciferase, electrophoretic mobility shift, and chromatin immunoprecipitation assays showed that CmBBX7 directly targets CmFTL1. In addition, we found that CmBBX7 and CmBBX8 interact to positively regulate the expression of CmFTL1 through binding to its promoter. Collectively, these results highlight CmBBX7 as a key cooperator in the BBX8–FT module to control chrysanthemum flowering. Graphical Abstract